Possibilidade para a sustentabilidade na Zona Costeira Paulista - Alcalá, Patricia (2013)
The research analyzes the precepts applied to a sustainable development in priority area for biodiversity conservation on account of its location. This means the Paulista Coastal Zone, registered as a National Heritage by the Brazilian constitution of 1988, covering the "Restinga", an ecosystem associated with the Atlantic Forest biome. Based on the concept of mosaic conservation with occupation, it interested bringing to light a case of study, the Acaraú Farm Project, located in Bertioga. The challenge of this project is the application of a development socially inclusive, environmentally sustainable and economically viable. The criteria for analysis of this case of study were: integrated application of legislation and scientific knowledge of geographic space with the use of reduced environmental resources. This discussion is necessary in order that the concept of sustainable development still presents an abstract appearance